2014
DOI: 10.9790/3008-09420106
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Annona muricata ethanolic leaf extract against Dimethylnitrosamine (DMN)-Induced Hepatotoxicity

Abstract: The present study was conducted to evaluate the protective role of ethanolic leaf extract of Annona muricata on dimethylnitrosamine (DMN)-induced hepatotoxicity in rat model. DMN administered rats (single dose orally, 12 mg/kg; on day 8) were pretreated with ethanolic leaf extract of Annona muricata (400 mg / kg body weight) for 7 days and sacrificed 48hrs after DMN intoxication. Results showed that DMN caused a marked rise in serum alanine aminotransferase (ALT), total cholesterol (TC), as well as marked decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
3
0
0
Order By: Relevance
“…In rats administered DMN-alone, the significant increase in total bilirubin level compared to control and extract pre-treated rats gives credence to our previous study where we reported increases in AST, ALT, ALP and GGT (Usunobun, 2014. The abnormal high level of serum total bilirubin indicates liver dysfunction and thus damaged structural integrity of the liver.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In rats administered DMN-alone, the significant increase in total bilirubin level compared to control and extract pre-treated rats gives credence to our previous study where we reported increases in AST, ALT, ALP and GGT (Usunobun, 2014. The abnormal high level of serum total bilirubin indicates liver dysfunction and thus damaged structural integrity of the liver.…”
Section: Discussionsupporting
confidence: 60%
“…However, Annona muricata pre-treatment prior to DMN administration significantly lowered the serum urea and creatinine levels, thus enhancing renal function. In this study, DMN decreased white blood cells WBCs, Platelets, RBCs, PCV, and Hb in DMN treated group compared to control groups similar to our previous study (Usunobun, 2014). However, pre-treatment with 400mg/kg Annona muricata prior to DMN administration significantly (P˂0.05) enhanced the hematological parameters, thus indicating that Annona muricata improve immunity function and decrease inflammation.…”
Section: Discussionsupporting
confidence: 51%
“…White blood cells play the main role in immune responses. These cells carry out the many tasks required to protect the body against disease-causing microbes and abnormal cells (Lee et al, 2012;Usunobun, 2014). In the present study, DMH increased the WBCs, lymphocytes and granulocytes in DMH alone treated group compared to control and extract pretreated and post treated groups.…”
Section: Olude O M; Chukwu O Jsupporting
confidence: 55%
“…This current study shows that ethanol extract of Annona muricata leaves have both combined anticarcinogenic and antioxidant activities that inhibited colon carcinogenesis and simultaneously suppress oxidative stress. The efficacy of EEAML on DMH induced colon carcinogenesis inhibition is likely boosted by its antioxidative action and presence of some compounds like acetogenins, flavonoids, tannins, proanthocyanidin, phenols, ferric acid reducing antioxidant potential of EEAML and DPPH radical scavenging activity of EEAML (Olude et al, 2020;Usunobun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%